Risk to sustainability of pest management tools in peanut. Issue 1 (21st May 2020) - Jordan, David L.; Dunne, Jeffrey; Stalker, H. Thomas; Shew, Barbara B.; Brandenburg, Rick L.; Anco, Dan; Mehl, Hillary; Taylor, Sally; Balota, Maria
Abstract: A diversity of pests can adversely affect peanut ( Arachis hypogaea L.) yield, quality, and financial return. Farmers rely heavily on applied chemicals to suppress many of the economically important pests present in peanut. The effectiveness of this approach to pest management may not be sustainable, however, due to evolved resistance in pests to chemicals, reluctance of basic chemical manufacturers to invest in product development because of the relatively small market for peanut compared with other crops, cost to initially register or re‐register chemicals, and the desire for peanut buyers and processors to capture international markets that may have varying agrochemical residue restrictions for peanut. Heavy reliance on chemical control could leave peanut production systems vulnerable to yield loss; thus, a more concerted research effort is needed to increase the number and availability of nonchemical tools that protect peanut from pests in order to ensure long‐term sustainability of peanut production systems.